Design, synthesis, and biological evaluation of novel triazoloquinazolinone derivatives as SHP2 protein inhibitors - Rongshuang Luo; Zhongyuan Wang; Dali Luo; Yumei Qin; Chunshen Zhao; Di Yang; Tian Lu; Zhixu Zhou; Zhuyan Huang (Taylor & Francis Group, 2021)
A novel series of triazoloquinazolinone derivatives were designed, synthesised, and evaluated for their in vitro biological activities against the SHP2 protein. Moreover, some compounds were evaluated against A375 cells. The results revealed that target compounds possessed moderate to excellent inhibitory activity against SHP2 protein, whereas compounds 12f, 12l, 12j, 17e, and 17f have strong antiproliferative activity on A375 cells. The compound 12l showed remarkable cytotoxicity against A375 cells and a strong inhibitory effect against SHP2 protein when compared with SHP244. The structure-activity relationships (SARs) indicated that electron-donating groups (EDGs) on phenyl rings are beneficial for improving the antitumor activity; compounds with a hydroxyl substituent at the 2-position of phenyl ring exhibited superior activities than compounds with a substituent at the 4-position. In addition, compound 12l displayed improved physicochemical properties as well as metabolic stability compared to SHP244. Our efforts identified 12l as a promising SHP2 protein inhibitor, warranting its further investigation.